Floristic composition of vegetable groups of oak plantations of Polisya of Ukraine after continuous cutting - Ivanyuk, I.D.; Ivanyuk, T.M. (Forestry, Forest, Paper and Woodworking Industry, 2019)
It is known that after continuous logging in the process of machinery during the harvesting of wood and mechanized soil preparation for the creation of forest crops of common oak, there is a violation of vegetation. The composition of the grass and shrub cover of forest areas is changing dramatically, so the study of the dynamics of the similarity of the floristic composition of plant communities at the site of continuous fellings and throughout the period of growth of oak plantations is relevant. The research was carried out on forest areas in the conditions of fresh co-soils of the state forestry enterprises of Central Polissya for which full geobotanical descriptions were made. It is established that within 1-3 years after continuous felling of submenopausal phytocenoses of oak forests in fresh soils of Central Polissya, which, for the most part, are buckthorn-lily-of-the-grass or mixed-grass-lily of the valley, dynamic plant groups begin to form. and meadow species leaving light-loving forests. In such phytocenoses, there are significant differences in the floristic composition of the grass-shrub layer in comparison with the composition of the same layer in the mother plantation. This condition is observed before the closure of the crowns and the formation of its own tent planting. Then there is a gradual restoration of the floristic composition of the grass-shrub tier, the species similarity of plant communities according to the Sorens-Chekanovsky index increases to 0.72 (compared to plantations 20-40 years of age) and to 0.66-0.68 compared to floristic composition of 80-110 annual plantations of oak. After 40 years of age, in the oak groves of fresh sogruds of Central Polissya, the floristic composition of plant groups is almost close to the composition typical of the grass-shrub layer of subclimax mother plantations.